Effects of Clostridium butyricum on Growth Performance, Intestinal Health, and Disease Resistance of Hybrid Grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) Fed with Cottonseed Protein Concentrate (CPC) Replacement of Fishmeal - Pan, Ling; Li, Weikang; Xie, Ruitao; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang (Aquaculture nutrition, 2023)
An 8-week feeding trial was conducted to investigate the effects of C. butyricum on the growth performance, microbiota, immunity response, and disease resistance in hybrid grouper fed with cottonseed protein concentrate (CPC) replacement of fishmeal. Six groups of isonitrogenous and isolipid diets were formulated including a positive control group (50% fishmeal, PC), a negative control group (CPC replaced 50% of fishmeal protein, NC), and Clostridium butyricum supplemented with 0.05% (C1, 5×108 CFU/kg), 0.2% (C2, 2×109 CFU/kg), 0.8% (C3, 8×109 CFU/kg), and 3.2% (C4, 3.2×1010 CFU/kg), respectively, to the NC group. The results showed that weight gain rate and specific growth rate were significantly higher in the C4 group than that in the NC group (P<0.05). After supplementation with C. butyricum, the amylase, lipase, and trypsin activities were significantly higher than the NC group (P<0.05; except group C1), and the same results were obtained for intestinal morphometry. The intestinal proinflammatory factors were significantly downregulated, and the anti-inflammatory factors were significantly upregulated in the C3 and C4 groups compared with the NC group after supplementation with 0.8%-3.2% C. butyricum (P<0.05). At the phylum level, the PC, NC, and C4 groups were dominated by the Firmicutes and the Proteobacteria. At the genus level, the relative abundance of Bacillus in the NC group was lower than that in the PC and C4 groups. After supplementation with C. butyricum, grouper in the C4 group showed significantly higher resistance to V. harveyi than the NC group (P<0.05). Above all, taking into account the effects of immunity and disease resistance, it was recommended to supplement 3.2% C. butyricum in the diet of grouper fed the replacement of 50% fishmeal protein by CPC.